Engineering Science / Fifth Edition - Bolton William (Elsevier - Newnes, 2006)
The most comprehensive engineering science text available - fully in line with the latest pre-degree course requirements. Preface, Basics, Statics, Stress and Strain, Linear Motion, Angular Motion, Dynamics, Energy, Heat, D.c. Circuits, Magnetism, Engineering Systems, Circuit Analysis, Semiconductors, Capacitance, Magnetic Flux, Alternating Current, Series a.c. Circuits, D.c. Circuit Analysis, D.c. Machines, Transients Parallel a.c. Circuits, Three-Phase a.c., Structures, Beams, Components, Circular Motion, Mechanical Power Transmission, Structural Members, Frictional Resistance, Angular Dynamics, Oscillations, Appendix: Calculus, Answers, Index.